KOLABORASI STAKEHOLDER DALAM SOSIALISASI TANGGAP DARURAT BENCANA: (Studi di Kabupaten Timor Tengah Selatan) - Boi Lopo Maksi Kase (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
Disaster emergency response is an action that involves stakeholders in conducting socialization so as to reduce disaster victims in Timor Tengah Selatan Regency. The collaborative process in emergency response socialization consists of face-to-face meetings, building trust, building commitment, mutual understanding, and interim results. Each stakeholder who collaborates takes their respective roles and functions at each stage of disaster response management above. One of the roles that stakeholders carry out is to carry out socialization, ranging from disaster mitigation, socialization about rescue and evacuation, to socialization about data validation for disaster victims. Supporting factors from within are the cooperation and awareness of all institutions, both government and private institutions as well as elements of the community who are aware of their respective duties and responsibilities and the need for collaboration in disaster management efforts, as well as the establishment of good communication between each stakeholder. The external supporting factor is the existence of training for disaster management that strengthens the competence of officers in dealing with natural disasters. Inhibiting factors that hinder stakeholder collaboration in socializing disaster emergency response in Timor Tengah Selatan Regency Geographical conditions, minimal budget, culture, imbalance of resources between stakeholders, and sophisticated equipment.